A community resource of experimental data for NMR / X‐ray crystal structure pairs. (22nd September 2015) - Everett, John K.; Tejero, Roberto; Murthy, Sarath B. K.; Acton, Thomas B.; Aramini, James M.; Baran, Michael C.; Benach, Jordi; Cort, John R.; Eletsky, Alexander; Forouhar, Farhad; Guan, Rongjin; Kuzin, Alexandre P.; et al.
Abstract: We have developed an online NMR / X‐ray Structure Pair Data Repository. The NIGMS Protein Structure Initiative (PSI) has provided many valuable reagents, 3D structures, and technologies for structural biology. The Northeast Structural Genomics Consortium was one of several PSI centers. NESG used both X‐ray crystallography and NMR spectroscopy for protein structure determination. A key goal of the PSI was to provide experimental structures for at least one representative of each of hundreds of targeted protein domain families. In some cases, structures for identical (or nearly identical) constructs were determined by both NMR and X‐ray crystallography. NMR spectroscopy and X‐ray diffraction data for 41 of these "NMR / X‐ray" structure pairs determined using conventional triple‐resonance NMR methods with extensive sidechain resonance assignments have been organized in an online NMR / X‐ray Structure Pair Data Repository. In addition, several NMR data sets for perdeuterated, methyl‐protonated protein samples are included in this repository. As an example of the utility of this repository, these data were used to revisit questions about the precision and accuracy of protein NMR structures first outlined by Levy and coworkers several years ago (Andrec et al ., Proteins 2007;69:449–465). These results demonstrate that the agreement between NMR and X‐ray crystal structures is improved using modern methods of protein NMR spectroscopy. The NMR / X‐ray Structure Pair Data Repository will provide a valuable resource for new computational NMR methods development.